Self-Management And Developing Countries - Adizes, Ichac (Universidad del Pacífico, 1975)
Given the limitations of traditional economic theory in its generalizations, some economists are searching new analytical frameworks to analyze social reality. Following the proposal of Jürgen Schuldt to integrate economics with political sociology, this article offers the first suggestions to achieve this synthesis.